Intrastromal autologous implantation of adipose derived adult stem cells for the management of established corneal scars - Jorge L. Alio del Barrio; Alberto Parafita-Fernandez; Daniel Gomez Plaza; Maria Eugenia Fernandez; Jorge L. Alio (American Journal of Ophthalmology Case Reports)
Purpose: To describe a case of well-documented corneal stroma transparency improvement following the intrastromal implantation of autologous adipose-derived mesenchymal stem cells (ADASC) in a keratoconic patient with established stromal scars. Observations: ADASC were isolated by elective liposuction, and a solution composed of 3x106 ADASC contained in 1mL saline was used to soak a corneal intrastromal pocket created with femtosecond laser at mid-depth. No signs of inflammation or rejection were observed. One year after surgery, we observed a complete restoration of the pre-existing corneal stroma scars, observed both clinically and by anterior segment OCT. The rest of the visual and topographic parameters did not show relevant changes except for the patient's refractive sphere. OCT showed a thin new layer of neocollagen deposited at the surgical plane. Total stroma optical density (OD) improved from 51.5 to 41.2 GSU, anterior stroma OD improved from 55.9 to 42.8 GSU, and posterior stroma OD improved from 46.9 to 39.6 GSU. Conclusions and importance: This clinical case provides new clinical evidence supporting the use of intrastromal mesenchymal stem cell implantation to solve or alleviate established corneal scars.